Cessation of pacing in super‐responders of cardiac resynchronization therapy: A randomized controlled trial. (25th September 2018) - Liang, Yixiu; Wang, Qingqing; Zhang, Mingliang; Wang, Jingfeng; Chen, Haiyan; Yu, Ziqing; Gong, Xue; Su, Yangang; Ge, Junbo
Abstract: Background: The consequence of cessation of biventricular pacing in super‐responders of cardiac resynchronization therapy (CRT) has not been fully investigated. Methods: In this prospective, single‐blinded clinical trial, 21 super‐responders were randomly assigned to the ceased pacing (CeP, 11 patients) group or the continued pacing (CoP, 10 patients) group. Patients randomized to the CeP group underwent cessation of biventricular pacing. New York Heart Association (NYHA) class, quality of life (QOL) assessed with Minnesota questionnaire, 6‐minute walking distance (6MWD), left ventricular end systolic volume (LVESV), left ventricular end‐diastolic volume (LVEDV), and left ventricular ejection fraction (LVEF) were compared between groups at 3‐ and 6‐month follow‐up. Results: No significant difference was observed between the CeP and CoP groups regarding NYHA class, QOL, 6MWD, LVESV, LVEDV, or LVEF after 3 months (all P > 0.05). After 6 months, there existed no significant difference between the CeP and CoP groups with regard to NYHA class, QOL, 6MWD, LVESV, and LVEDV (all P > 0.05); however, LVEF was significantly lower in the CeP group than that of the CoP group (0.49 ± 0.10 vs 0.60 ± 0.11, P = 0.04), and LVEF was significantly reduced in the CeP group compared with the baseline value at randomization (0.49 ± 0.10 vs 0.54 ± 0.06, P = 0.04). Conclusion: LVEF was significantly reduced in super‐responders of CRT 6 months after cessation of pacing. Super‐responders to CRT should receive continued, long‐term pacing to preserve recovered LV function.